Bone−Patellar Tendon−Bone Autograft in Anterior Cruciate Ligament Reconstruction: A Comprehensive Approach - Ayham Jaber, M.D.; Colin Murphy, M.D.; Christopher J. Hawryluk, M.B.S.; Lana Arbili, M.D.; Maximilian Hinz, M.D.; Natalie Cortes, M.S.; Peter J. Millett, M.D., M.Sc. (Arthroscopy Techniques)
Anterior cruciate ligament reconstruction using a bone–patellar tendon–bone autograft is widely regarded as the graft of choice for many sports medicine surgeons for young, active patients with anterior cruciate ligament injuries. It is favored for use in athletes because of its high return-to-play rates and low re-rupture rates. Despite its benefits, there are many pitfalls in the surgical technique, and the use of a careful surgical technique can avoid them. This article describes our preferred technique.